Estimation of Stature from Nasal Dimensions (Medico Legal Update, 2021)
The objective of this study was to estimate stature from nasal measurements in South Indian population.The study was done using standard measuring apparatus measuring tape and vernier calipers including bothmales and females.Regression formula and correlation was derived between nasal dimensions and stature. In thisstudy, regression formula is derived with three variables generalized for both males and females, S=118.005+6.804NL+4.003NW+0.254NH ? 9.70100. Linear Regression equation for males and females havebeen derived separately with each of the nasal parameters. In conclusion nasal measurements can be aneffective tool in estimating stature.